2002
DOI: 10.1089/10966210252785097
|View full text |Cite
|
Sign up to set email alerts
|

Methadone Use in Cancer Patients with Pain: A Review

Abstract: In recent years a better understanding of the pharmacologic and pharmacokinetic properties of methadone, including equianalgesic ratios has led to its increased use as a second line opioid for the treatment of pain in patients with cancer. Methadone may be an important alternative for those who have side effects related to the use of other opioids because it has no known active metabolites, is well absorbed by oral and rectal routes, and also has the advantage of very low cost. However, it has a long, unpredic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
128
0
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(131 citation statements)
references
References 62 publications
1
128
0
2
Order By: Relevance
“…These methadone clinics are government funded operations and use different urine drug testing agencies. Second, Methadone is commonly used to treat chronic pain in the U.S. due to the following three reasons: (a) Methadone is more potent than most opioids (Bruera and Sweeney, 2002). In the setting of chronic pain, patients have built tolerance to other opioids and reqire higher doses and number of tablets.…”
Section: Discussionmentioning
confidence: 99%
“…These methadone clinics are government funded operations and use different urine drug testing agencies. Second, Methadone is commonly used to treat chronic pain in the U.S. due to the following three reasons: (a) Methadone is more potent than most opioids (Bruera and Sweeney, 2002). In the setting of chronic pain, patients have built tolerance to other opioids and reqire higher doses and number of tablets.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has recently been 'rediscovered' as an analgesic in the treatment of chronic pain 2 and cancer pain. 3 A recent survey revealed that the prevalence of chronic pain in Canada is 29%. Of those chronic pain sufferers taking medications, 22% take opioids as an analgesic.…”
Section: Conclusion : La Méthadone Est Un Opiacé Aux Propriétés Complmentioning
confidence: 99%
“…Methadone in the form of the isolated R-Met (l-isomer) is available in Germany. 3,12 The S-Met enantiomer is inactive as a µ agonist. Nonetheless, it is a noncompetitive N-methyl-d-aspartate (NMDA) antagonist and prevents 5-hydoxytryptamine and norepinephrine reuptake.…”
Section: Conclusion : La Méthadone Est Un Opiacé Aux Propriétés Complmentioning
confidence: 99%
“…In addicts, methadone may be an important alternative to other opioids, because it has no known active metabolites and less side effects [18]. It is well absorbed by oral and rectal routes, and also has the advantage of very low cost.…”
Section: Cancer Pain and Addictionmentioning
confidence: 99%